Calves Persistently Infected by Bovine Viral Diarrhea Virus and Human Autoimmune Polyglandular Syndrome Type-1: What to learn from two natural models of impaired immunological tolerance? A review (2023)
ABSTRACT: Human clinicians know about autoimmune polyglandular syndrome type 1 (APS-1) but do not know about bovine viral diarrhea virus (BVDV) persistently infected (PI) calves. These two clinical entities have as a common factor that they represent two natural models of immune tolerance failure occurring during thymocyte maturation in fetal life. In APS-1, mutations of the autoimmune regulatory gene (AIRE gene) are responsible for the reduction of promiscuous expression of tissue-specific antigens (TSA) by medullary thymus epithelial cells (mTECs) during presentation of self-antigens to single negative (SN) T cells. Such reduction results in the generation of autoreactive T cell clones that colonize secondary lymphoid tissues and cause APS-1 in postnatal life. APS-1 patients are the evidence of the effects of these mutations and support the importance of PGE during the generation of immune tolerance. Heifers or pregnant cows infected with a non-cytopathic strain of BVDV during the period of intrathymic maturation of fetal T lymphocytes generate PI calves. Although the molecular mechanism of PI calf generation is still unsolved, viral antigens presented as self-antigens during the developing T-cells' intrathymic maturation appear to be responsible. Although there is no published work on AIRE gene expression during T cell maturation in bovine fetuses, the high homology in nucleotide and amino acid sequence of the AIRE gene and protein between humans and bovines, and high conservation of the gene across the species, supports that the bovine AIRE gene functions similarly as in humans. In this paper, we discuss similarities between APS-1 patients and PI calves' clinical signs. We propose that there must be processes related to reduced PGE in bovine fetal mTECs caused by the virus, resulting in autoreactive T cells responsible for clinical signs of PI calf cases. In the absence of experimental evidence on the generation of PI animals, the knowledge achieved in APS-1 allows us to propose experimental models to fill these knowledge gaps. Accordingly, knowledge gained about AIRE gene mutations could contribute to understanding the calves and APS-1: natural mistakes of immune tolerance. mechanisms of tolerance against viral infections in cattle and other animal species and their effect on postnatal life, to investigate prevention or treatment alternatives.